SYSTEMIC INFLAMMATION IN COMORBID METABOLIC SYNDROME AND VITILIGO: A REGRESSION ANALYSIS OF RISK FACTORS! - SINGH, PAVAN K; KAUSHIK, KANISHK U; BHARGAVA, RAHUL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Systemic inflammatory markers are often raised in comorbid metabolic syndrome (MetS) and vitiligo. Why some patients with vitiligo develop MetS while others do not remain to be elucidated. This study aimed to identify independent risk factors for MetS development in vitiligo patients. Methods: In this prospective study, disease characteristics (disease duration, severity, and subtype) and high-sensitivity C-reactive protein (hs-CRP) were compared between vitiligo patients (n=100) with and without MetS. Multivariate logistic regression of potential risk factors for MetS was done after adjusting for potential confounders (such as waist circumference, basal metabolic rate, serum lipids, blood pressure, and fasting blood sugar). The performance of these parameters (hs-CRP, age, disease duration, and severity) in predicting MetS development was ascertained by the area under the receiver operating characteristic curve (ROC). Results: Vitiligo patients with MetS had a significantly longer (p<0.001) disease duration as compared to those without MetS (56±16 versus 14±12 months). On regression analysis, inflammatory markers (hs-CRP) had significantly higher odds (odds ratio [OR]=5.1) as compared to demographic factors such as gender (OR=3.1) and disease factors such as disease duration (OR=2.4) and disease severity (OR=1.8) of developing MetS. On ROC curve analysis, the performance of these parameters for MetS was hs-CRP>Vitiligo Area Scoring Index score>disease duration >increasing age (Area under the curve=0.952, 0.905, 0.851, and 0.697, respectively). The cutoff value of hs-CRP was 6.42 ug/mL. Conclusion: Elevated hs-CRP has the highest predictive value for MetS development in vitiligo. Systemic inflammation may be the driving force for MetS development.